Artificial Intelligence in Accounting - Review of Research Areas - Agnieszka JUDKOWIAK; Beata ZALESKA (Communications of International Proceedings, 2022)
The implementation of innovative technological solutions in the field of artificial intelligence has recently had a significant impact on the increase in the popularity of this issue among researchers from various fields of science. The number of publications related to the subject of artificial intelligence in accounting, which is increasing every year, covers a number of different aspects. The aim of the article was to present aspects of research on artificial intelligence in accounting and to group them according to research areas. The study used the literature review method. The research technique was the mapping technique. The analysis of the literature covered the years 2017-2021. On the basis of the analysis, four leading thematic areas were selected, covering numerous aspects related to artificial intelligence in accounting. The results of the analysis will contribute to a better understanding of the implementation of artificial intelligence in accounting and may constitute the basis for further in-depth analyzes.
Keywords: artificial intelligence; IT; accounting